Novel strategies to improve chicken performance and welfare by unveiling host-microbiota interactions through hologenomics - Tous, Núria; Marcos, Sofia; Goodarzi Boroojeni, Farshad; Pérez de Rozas, Ana; Zentek, Jürgen; Estonba, Andone; Sandvang, Dorthe; Gilbert, M. Thomas P.; Esteve-Garcia, Enric; Finn, Robert; Alberdi, Antton; Tarradas, Joan (Frontiers in Physiology, 2022)
Fast optimisation of farming practises is essential to meet environmental sustainability challenges. Hologenomics, the joint study of the genomic features of animals and the microbial communities associated with them, opens new avenues to obtain in-depth knowledge on how host-microbiota interactions affect animal performance and welfare, and in doing so, improve the quality and sustainability of animal production. Here, we introduce the animal trials conducted with broiler chickens in the H2020 project HoloFood, and our strategy to implement hologenomic analyses in light of the initial results, which despite yielding negligible effects of tested feed additives, provide relevant information to understand how host genomic features, microbiota development dynamics and host-microbiota interactions shape animal welfare and performance. We report the most relevant results, propose hypotheses to explain the observed patterns, and outline how these questions will be addressed through the generation and analysis of animal-microbiota multi-omic data during the HoloFood project.